Wind induced dynamic response and fatigue assessment – Nonlinear time domain versus linear stochastic analysis. (December 2021) - Jia, Junbo
Abstract: By performing the nonlinear dynamic analysis and calculating the wind induced fatigue damage, this paper compares the fatigue calculation results with that obtained from a linear stochastic dynamic analysis in frequency domain. It is noticed that, since linear frequency domain analysis often involves a linearization of relevant non-linear load effects, associated with non-linear drag, coherence of wind loading in space, large deformation and local plasticity development, into the linear solution of dynamic equilibrium equations, and also because the power spectrum of critical stress (quasi-static and dynamic) due to wind loading may not be narrow-banded, initiated by the influence of the background components of incident turbulence, across wind-induced vibrations, wind directional effects and structural damping and so on, the inappropriate use of the linear spectral method developed for Gaussian processes can mis-predict the dynamic response, leading to a significant bias in the fatigue damage assessment. It is found that the disadvantages of the linear method aforementioned have to be compromised by additional assumption of uncertainties implemented in calculating dynamic response, often resulting in an over-conservative evaluation in fatigue damage estimation. The wind induced fatigue calculation procedure using non-linear dynamic analysis can be widely adopted for various types of structures, which can significantly reduce the uncertainties without compromising the safety requirement.